Sounds of the northern Andes: the calls of a diverse and endangered frog community (Amphibia, Anura) from Ecuador - Diego Batallas; Rafael Márquez; Juan M. Guayasamin (ZooKeys)
The emission of calls is one of the most distinctive and important reproductive traits in anurans. Given the biological significance of vocalizations, this trait is also useful for identification proposes and is key in recognizing cryptic diversity. However, the majority of the calls from tropical ecosystems, especially in the high Andean mountains, are unknown. Between 2016 and 2021, a total of 14 expeditions were conducted to the forests and moorlands of the eastern and western Andean Mountain range of the province of Carchi-Ecuador, at elevations ranging from 2694 to 3848 m a.s.l. The objective of these expeditions was to record the calls of the anuran fauna present in these ecosystems. In total, 30 anuran species were recorded, and calls of 20 species were described, 15 of which are described and reported for the first time in the present study. The call of Hyloxalus delatorreae, a critically endangered species, is described with a remarkable recording of the call of Niceforonia brunnea, a species considered mute. In addition, nine are candidate species, including the first record of Pristimantis farisorum for Ecuador. This study represents the most comprehensive and accurate acoustic documentation of a highland community, which will facilitate taxonomic and conservation work in the area.